Prevalence of Chronic Diseases and Quality of Life among Elderly People of Kathmandu, Nepal - Shrestha, Supri Raj; Silvanus, Vinutha; Joshi, Deepak Raj (Nepal Medical College Journal, 2022)
The world is experiencing growth in the number and proportion of older population and their population are found to be growing much faster in the developing countries. The ageing population tends to have a higher prevalence of chronic diseases worldwide. These problems can lead to decrease in quality of life of elderly. The current study aimed to study the prevalence of chronic diseases and quality of life among elderly people of Kathmandu. This is a community based cross sectional study done among 200 elderly people who are more than or equal to 60 years at Budanilkantha Municipality-13, Chunikhel. The information was obtained using semi structured questionnaire. A standardized tool of the WHOQOL‑BREF questionnaire was used to assess the quality of life (QoL) of participants. Among various chronic diseases, the prevalence of hypertension was highest. The mean score of environment domain was better than physical health, psychological and social relationships domain respectively. QoL was statistically significant with increase in literacy status, education of head of family and their involvement in decision making. The overall mean score of QoL among both the diseased and not diseased elderly were similar. Thus, the present study provides valuable information regarding the QoL of the elderly in the community.